2021
DOI: 10.15252/emmm.202012433
|View full text |Cite
|
Sign up to set email alerts
|

The enhancement of activity rescues the establishment of Mecp2 null neuronal phenotypes

Abstract: MECP2 mutations cause Rett syndrome (RTT), a severe and progressive neurodevelopmental disorder mainly affecting females. Although RTT patients exhibit delayed onset of symptoms, several evidences demonstrate that MeCP2 deficiency alters early development of the brain. Indeed, during early maturation, Mecp2 null cortical neurons display widespread transcriptional changes, reduced activity, and defective morphology. It has been proposed that during brain development these elements are linked in a feed‐forward c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 93 publications
0
14
0
Order By: Relevance
“…Early interventions aimed at increasing neuronal activity mitigate disease onset in both male and female mouse models for Rett syndrome. Early administration of Ampakine CX546, a positive modulator of AMPA receptors, from postnatal days 3-9 in male Mecp2 -null mice enhances neuronal activity, prolongs lifespan, delays disease progression, and rescues both motor abilities and spatial memory (Scaramuzza et al, 2021). In Het females, repetitive motor training enhances neuronal activity of task-specific neurons and improves both spatial memory and motor function well into adulthood (Achilly et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Early interventions aimed at increasing neuronal activity mitigate disease onset in both male and female mouse models for Rett syndrome. Early administration of Ampakine CX546, a positive modulator of AMPA receptors, from postnatal days 3-9 in male Mecp2 -null mice enhances neuronal activity, prolongs lifespan, delays disease progression, and rescues both motor abilities and spatial memory (Scaramuzza et al, 2021). In Het females, repetitive motor training enhances neuronal activity of task-specific neurons and improves both spatial memory and motor function well into adulthood (Achilly et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The calcium-target and calcium-regulating signature genes separated the Rett syndrome samples from the healthy control samples in the PC1-PC2 space well (Figure 2A,B). Unsupervised analysis of differentially expressed genes in the mouse model of Rett syndrome did not reveal significantly enriched calcium-related pathways (Supplementary Figure S1A,B); however, it has been previously shown that calcium signaling is implicated in RTT pathology [26,27]. Focusing on the calcium-related differentially expressed genes utilizing the CaDeGB database, we found that in Mecp2-KO mice, 12.5% (four genes) of all differentially expressed genes were calcium-related (Table 2, Supplementary Table S1).…”
Section: Rett Syndrome (Gse105045 Gse128380)mentioning
confidence: 85%
“…Early interventions aimed at increasing neuronal activity mitigate disease onset in both male and female mouse models for Rett syndrome. Early administration of Ampakine CX546, a positive modulator of AMPA receptors, from postnatal days 3–9 in male Mecp2 ‐null mice enhances neuronal activity, prolongs lifespan, delays disease progression, and rescues both motor abilities and spatial memory (Scaramuzza et al, 2021). In Het females, repetitive motor training enhances neuronal activity of task‐specific neurons and improves both spatial memory and motor function well into adulthood (Achilly et al, 2021).…”
Section: Discussionmentioning
confidence: 99%